Unravelling the shift: exploring consumers' adoption or resistance of E-Pharmacy through behavioural reasoning theory - Agyemang Kwasi Sampene; Cai Li; John Wiredu (BMC, 2024)
Abstract In the ever-evolving nature of the healthcare sector, the advent of electronic-Pharmacy introduces a dynamic shift in how consumers acquire and access medical and pharmaceutical products. The research utilized the behaviour reasoning theory. The study evaluated the reasons for adopting and against adopting electronic-Pharmacy. By employing the qualitative approach, this study unravels rich contextual and narrative insights, shedding light on the complexities of individual decision-making processes. The study received responses from 28 through an in-depth interview, and thematic data analysis was employed for the data analysis. The outcome of the research is summarized as follows. The respondents indicated that essential reasons for adopting electronic pharmacy services include convenience and accessibility, prescription management, cost and affordability, logistics, and timely delivery. On the other hand, the reasons against adoption include trust and security concerns, regulatory challenges and legal uncertainties, lack of internet access and privacy concerns. As technology changes healthcare delivery, this research closes the knowledge gap between theory and practice by offering crucial insights into the behavioural aspects influencing electronic-Pharmacy adoption or resistance. The findings are anticipated to significantly impact the academic discourse surrounding electronic-health and the practical implementation of strategies to enhance the integration of electronic-Pharmacy services into conventional healthcare systems.